2019
DOI: 10.1021/acsmaterialslett.9b00128
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Triggered Phase Transition in Cesium Lead Halide Perovskite Nanocrystals

Abstract: All-inorganic perovskite nanocrystals (NCs) have emerged as a class of low-cost and high-efficiency light-emitting materials. However, the structure and phase transition behavior of these NCs remain poorly understood. Here, we provide unambiguous evidence that all these properties are associated with structural defects in NCs. Using CsPbCl 3 NCs as a model system, we find that the cubic subdomains in highly defective NCs gradually convert to the orthorhombic upon cooling room-temperature quasi-cubic NCs, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 49 publications
5
67
0
Order By: Relevance
“…When the temperature was further increased to be above 300 K, Li et al 80 found out that the inorganic perovskite NCs could be thermally deteriorated to cause an irreversible quench in the PL intensities. The temperaturedependent optical properties are also strongly dependent on the existence of defect sites, which have been shown by Ma et al 81 to cause a phase transition from cubic to orthorhombic crystal structures upon cooling all-inorganic perovskite NCs from room temperature.…”
Section: Fundamental Optical Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…When the temperature was further increased to be above 300 K, Li et al 80 found out that the inorganic perovskite NCs could be thermally deteriorated to cause an irreversible quench in the PL intensities. The temperaturedependent optical properties are also strongly dependent on the existence of defect sites, which have been shown by Ma et al 81 to cause a phase transition from cubic to orthorhombic crystal structures upon cooling all-inorganic perovskite NCs from room temperature.…”
Section: Fundamental Optical Propertiesmentioning
confidence: 96%
“…With the increasing temperatures, most of the studied perovskite NCs demonstrated a blueshift in the PL peaks with broadened linewidths, as a joint effect of lattice expansion and exciton-phonon coupling. [78][79][80][81] In a very rare occasion, Wei et al 79 reported an anomalous redshift observed at 220 K in the PL peaks of CsPbBr 3 NC ensembles, which was attributed to the electronphonon coupling effect. When the temperature was further increased to be above 300 K, Li et al 80 found out that the inorganic perovskite NCs could be thermally deteriorated to cause an irreversible quench in the PL intensities.…”
Section: Fundamental Optical Propertiesmentioning
confidence: 99%
“…Reproduced with permission. [ 115 ] Copyright 2019, American Chemical Society. d) The defect formation energies of CsPbI 3 as a function of Fermi level between the valence band maximum and conduction band minimum of native point defects calculated under lead‐rich (left) and lead‐poor (right) growth conditions.…”
Section: Phase Stability Mechanism and Physical Properties Of Cspbi3 mentioning
confidence: 99%
“…used the case of CsPbCl 3 NCs and revealed that the structural defects dictated the structure and phase transition behaviors of all‐inorganic perovskite NCs. [ 115 ] They found that upon cooling the room temperature quasi‐cubic NCs, the cubic subdomains in the highly defective CsPbCl 3 NCs gradually converted to orthorhombic phase, while the high‐quality NCs, with mixed cubic and orthorhombic subdomains at room temperature, exhibited a significant resistance for such a phase transition (Figure 8c). Importantly, this defect‐triggered phase transition also exists in other all‐inorganic halide perovskite NCs including CsPbI 3 and CsPbBr 3 .…”
Section: Phase Stability Mechanism and Physical Properties Of Cspbi3 mentioning
confidence: 99%
“…In fact, such significantly reduced defect density in the CsPbI 3 is not only favored for high‐performance perovskite photoelectronic devices, but also beneficial to enhancing the photoactive phase stability via increasing the phase transition energy barrier from black phase to non‐photoactive yellow phase. [ 39,43 ]…”
Section: Figurementioning
confidence: 99%